Enhancing Students' Disaster Knowledge with BPBD Socialization Programs and Innovative Essay Writing Projects at SMAN 4 Semarang - Izzuddin Muhammad; Vina Nurul Husna (Universitas Lambung Mangkurat, 2025)
This study aims to enhance students' disaster knowledge through a BPBD socialization program and disaster research activities by writing innovative scientific essays. The research subjects were class XI Socrates 1 students at SMAN 4 Semarang. This research employed a quantitative method with a pre-experimental one-group pretest-posttest design. The activity stages included disaster preparedness socialization, scientific essay workshop, essay writing assistance, and evaluation through an essay presentation and post-test assessment. Data were collected using test instruments and essay assessment sheets in a Likert scale, then analyzed using descriptive percentages, N-Gain scores, and the Wilcoxon Signed-Rank Test. The results showed a 24% increase in students' disaster knowledge after participating in the program. The N-Gain score reached 60%, which suggests that the program implementation was moderately effective in improving students' knowledge. Furthermore, the Wilcoxon test results showed a significance p-value of less than 0.05, indicating a significant difference in students' learning outcomes before and after participating in the program. These findings conclude that integrating BPBD disaster preparedness outreach programs and disaster research into Geography education effectively enhances students' disaster knowledge.